ALKALINE PHOSPHATASE – A DIAGNOSTIC MARKER OF PERIODONTITIS IN POSTMENOPAUSAL WOMEN – A. B. OCHEMICAL STUDY - Ramesh, Amitha; Bhandary, Rahul; Thomas, Biju; D'Souza, Sheehan R.; Kumari, Suchetha (Journal of Health and Allied Sciences NU, 2013)
Background and objective: Periodontal disease is one of the common inflammatory diseases with complex etiology and is multifactorial in origin.Several enzymes are evaluated for the early diagnosis of periodontal disease. The enzyme ALP plays a role in bone metabolism. In the periodontium, ALP is very important enzyme as it is part of normal turnover of periodontal ligament, root cementum, and bone homeostasis. The deficiency of estrogen in women at menopause is contributing factor to osteoporosis and considered one of the risk factors for periodontal disease. It has been hypothesized that osteoporosis decreases alveolar bone density and in turn increases its susceptibility to resorption due to periodontal inflammation. Accelerated bone loss in menopause is related to increased bone turnover. This is accompanied by increased levels of biochemical markers such as Alkaline Phosphatase. Alteration in salivary Alkaline Phosphatase levels might be expected as an indication of periodontal disease activity.Methods: The study included 40 subjects, 20 in each group in the age group of 50-60 years. Group 1 comprised of 20 Postmenopausal women without chronic periodontitis. Group 2 comprised of 20 Postmenopausal women with chronic periodontitis. Each saliva sample was estimated for ALP levels.Results: The present study showed significant increase in Alkaline Phosphatase in postmenopausal women with periodontitis (Group 2) with p value <0.0001.Interpretation and conclusion: Alkaline phosphatase can be used as a diagnostic marker of Periodontitis in postmenopausal women. However ALP cannot be solely responsible for Periodontitis but it can be used as a additional aid in diagnosing Periodontitis.
Keywords: Alkaline phosphatise; Periodontitis